2005
DOI: 10.1097/01.mbc.0000161570.04883.25
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of molecular defect of 13387-9delG mutated antithrombin in inherited type I antithrombin deficiency

Abstract: As a major physiological inhibitor of thrombin and other coagulation proteases, antithrombin (AT) plays an important role in the maintenance of normal hemostasis and its deficiency is associated with a predisposition for familial venous thromboembolic disease. Recently, we found a novel mutation (13387-9delG) in the antithrombin gene that is associated with type I AT deficiency. To examine the molecular pathologic mechanism of this mutation causing type I AT deficiency, the wild-type and the mutant AT construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Mutations in the PROC and SERPINC1 were identified as previously described. 29,30 PROS1 Messenger Ribonucleic Acid Analysis and In Silico Analysis PROS1 messenger ribonucleic acid (mRNA) analysis was performed in proband 28 with a novel heterozygote splice site mutation c.1871-2A > G to identify its effect on normal transcription. The following primers: forward 5′-GTGCCCTTT-GCTGTGTCCT-3′, reverse 5′-CACCATCTCTTCTGCCTTC-3′, were used to amplify the sequence from exon 13 to 15 of PROS1.…”
Section: Genetic Analysis Of Pros1mentioning
confidence: 99%
“…Mutations in the PROC and SERPINC1 were identified as previously described. 29,30 PROS1 Messenger Ribonucleic Acid Analysis and In Silico Analysis PROS1 messenger ribonucleic acid (mRNA) analysis was performed in proband 28 with a novel heterozygote splice site mutation c.1871-2A > G to identify its effect on normal transcription. The following primers: forward 5′-GTGCCCTTT-GCTGTGTCCT-3′, reverse 5′-CACCATCTCTTCTGCCTTC-3′, were used to amplify the sequence from exon 13 to 15 of PROS1.…”
Section: Genetic Analysis Of Pros1mentioning
confidence: 99%
“…For example, p.Cys127Arg causes the rupture of disulfide bonds between Cys53-Cys127, significantly slows the rate of AT secretion, and persists in the intracellular reticulum in the form of oligosaccharides, which cause AT deficiency [ 57 ]. Mutations 13,387-9delG and c.964A > T (p.Lys322*) cause breakage of the disulfide bond between Cys279 and Cys462, impairing secretion and structural stability of AT-truncated proteins degraded intracellularly [ 58 , 59 ]. In addition, AT protein truncation caused by c.964A > T (p.Lys322*) led to the loss of the P1-P1′(Arg393-Ser394) bond, which does not act as an inactivated protease [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study by Michiels JJ et al pointed out that the absence of cross-reactive substances in the patients’ plasma indicated that p.Arg197stop either prevented the formation of stable mRNA or the translated peptide was rapidly degraded ( Michiels et al, 1995 ). It has been reported that the 13387-9delG mutation resulted in the loss of the disulfide bond between Cys247 and Cys430, impairing the secretion and stability of the truncated AT protein associated with intracellular degradation ( Wang et al, 2005 ). Since both c.964A > T (p.Lys322stop) and 13387-9delG mutations will cause the loss of the disulfide bond between Cys247 and Cys430, we assumed that c.964A > T (p.Lys322stop) caused the reduction of AT:A and AT:Ag by the same mechanism as 13387-9delG.…”
Section: Discussionmentioning
confidence: 99%